2013
DOI: 10.3389/fnhum.2013.00775
|View full text |Cite
|
Sign up to set email alerts
|

On ERPs detection in disorders of consciousness rehabilitation

Abstract: Disorders of Consciousness (DOC) like Vegetative State (VS), and Minimally Conscious State (MCS) are clinical conditions characterized by the absence or intermittent behavioral responsiveness. A neurophysiological monitoring of parameters like Event-Related Potentials (ERPs) could be a first step to follow-up the clinical evolution of these patients during their rehabilitation phase. Eleven patients diagnosed as VS (n = 8) and MCS (n = 3) by means of the JFK Coma Recovery Scale Revised (CRS-R) underwent scalp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 60 publications
3
80
0
1
Order By: Relevance
“…Of course, it is reasonable to assume that false positive results can occur with passive paradigms, but at present their frequency is unknown. However, serial assessments, although rarely performed, may increase the diagnostic yield and reveal signs of consciousness in passive and active paradigms in patients who initially are without such signs 11 15 25 40…”
Section: Discussionmentioning
confidence: 99%
“…Of course, it is reasonable to assume that false positive results can occur with passive paradigms, but at present their frequency is unknown. However, serial assessments, although rarely performed, may increase the diagnostic yield and reveal signs of consciousness in passive and active paradigms in patients who initially are without such signs 11 15 25 40…”
Section: Discussionmentioning
confidence: 99%
“…The P300 has been shown to predict the outcome of patients in low responsive state (Daltrozzo et al, 2007) or coma (Morlet and Fischer, 2014). It can provide information on conscious and unconscious cognitive functions (Risetti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of the P300 to distinguish between VS/UWS and MCS has shown contradictory results: some studies have found some differences in this ERP between both groups (Schnakers et al, 2008b; Cavinato et al, 2011; Risetti et al, 2013), while others did not (Kotchoubey et al, 2005; Perrin et al, 2006; Fischer et al, 2010; Real et al, 2016). Covert response to commands in VS/UWS patients has been reported with this ERP component (Chennu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%